Microbial community and fermentation characteristic of whole-crop wheat silage treated by lactic acid bacteria and Artemisia argyi during ensiling and aerobic exposure - Wang, Zhenyu; Tan, Zhongfang; Wu, Guofang; Wang, Lei; Qin, Guangyong; Wang, Yanping; Pang, Huili (Frontiers in Microbiology, 2022)
Whole crop wheat silage (WCWS) is an excellent feed material for ruminants. However, microbial fermentation during silage production consumes valuable nutrients, decreasing the quality of silage. The main objective of this study was to assess how the addition of increasing amounts of Artemisia argyi (AA) affected fermentation quality, microbial composition and mycotoxin production in whole crop wheat at dough stage (WCWD) silage during ensiling to aerobic exposure compared with Lactiplantibacillus buchneri (LB). The addition of 20% AA, resulted in a lower pH and higher lactic acid content, were found in silage treated by 20% AA, and an obvious increase in the relative abundance of Lactobacillus was detected in silages treated with LB and 20% AA, respectively. Meanwhile, inoculation with 20% AA decreased the abundance of harmful microorganisms, including Acinetobacter, Enterobacter and Aspergillus. It also reduced the contents of mycotoxins, Aflatoxin B1 (AFB1) and deoxynivalenol (DON) during ensiling and aerobic exposure. These results confirmed that WCWD treated by 20% AA could improve the fermentation quality and enhance the aerobic stability of silage.